Solution of infinite system of ordinary differential equations and fractional hybrid differential equations via measure of noncompactness. Issue 1 (11th December 2019) - Zada, Mian Bahadur; Sarwar, Muhammad; Nashine, Hemant Kumar
ABSTRACT: In this work, we use the notion of convex power condensing mapping under measure of noncompactness in locally convex spaces and establish some new coupled fixed point results. The results proved herein are the generalization and extension of some widely known results in the existing literature. Furthermore, we apply our results for the existence of solution to infinite system of ordinary differential equations and system of fractional hybrid differential equations.